Q. 154.4( 24 Votes )

# If m = (cos θ – s

Answer :

Given: m = (cos θ – sin θ)

n = (cos θ + sin θ)

Now, =

Multiply numerator and denominator by cos θ – sin θ :

Therefore, =

=

Now, =

Multiply numerator and denominator by cos θ + sin θ :

Therefore, =

=

Now, consider =

=

=

=

Divide numerator and denominator by cos θ:

=

=

Therefore, =

Hence, proved.

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Trigonometric Identities39 mins

Trigonometric Identities-II43 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation